Multiple visceral venous thromboses associated with oral contraceptive use - Kamel El-Reshaid; Shaikha Al-Bader; Hatem Sallam (Saudi Journal of Kidney Diseases and Transplantation, 2016)
Peripheral venous thromboembolism (VTE) is a known complication of oral contraceptive drugs (OCs), yet its association with visceral VTE is rarely reported. We describe a 21-year-old female patient who presented with sudden left loin pain. Plain computed tomography (CT) urography did not show kidney lesion but was suspicious of left renal vein thrombosis. Contrast study confirmed the diagnosis and also disclosed thrombosis of the splenic and left ovarian veins. The patient did not have a family history or laboratory evidence of hypercoagulable disorder. An OC was the only medication she had received in the previous three months. The OC was discontinued, and the patient was anticoagulated with heparin and discharged home on warfarin for a total period of six months. Subsequent CT study with contrast, one month later, showed complete resolution of the thrombosis without any visceral abnormality.